The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1160/th17-02-0079
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factor and protease pathways in thrombosis and cardiovascular disease

Abstract: SummaryThe biochemical characterisation of the proteolytic pathways that constitute blood coagulation was one of the most relevant achievements in biomedical research during the second half of the 20th century. Understanding these pathways was of crucial importance for improving global health through application in haemostasis and thrombosis pathologies. Immediately after the cloning of the genes corresponding to these proteins, mutations were discovered in them that were associated with imbalances in haemosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 70 publications
1
37
0
Order By: Relevance
“…Adapted from Weitz, JI. Thromb Haemost 2014;112:924–31 and Ten Cate, H. Thromb Haemost 2017;117:1265–71 . PAR, protease‐activated receptor; TF, tissue factor; vWF, von Willebrand factor…”
Section: Pathophysiologymentioning
confidence: 99%
“…Adapted from Weitz, JI. Thromb Haemost 2014;112:924–31 and Ten Cate, H. Thromb Haemost 2017;117:1265–71 . PAR, protease‐activated receptor; TF, tissue factor; vWF, von Willebrand factor…”
Section: Pathophysiologymentioning
confidence: 99%
“…One of the most well studied aptamers is HD1, an aptamer targeting the exosite I moiety of thrombin (an important haemostatic protein) that was first described in 1992 [ 10 ]. Thrombin is central to the blood coagulation process, cleaving fibrinogen to fibrin, which forms the basis of a blood clot, amongst a number of other important activation steps [ 11 ]. The discovery of HD1 was soon followed by the development of a second thrombin targeting aptamer in 1997, HD22, which targets exosite II of the thrombin molecule [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was suggested that a possible reason of PC reduction after bariatric surgery is due to a vitamin K dysregulation caused by malabsorption due to the surgical procedure [ 29 ]. We therefore measured PT, as this reflects the activities of the vitamin K dependent factors VII, X and II [ 31 ]. Furthermore, a strong correlation of factor VII activity with activity of PC, was shown [ 27 ].…”
Section: Discussionmentioning
confidence: 99%